The Role of Sports Media in Exercising for Males Over the Age of Forty - Mohamed Adnan Hussein Aldulimi; Muthana Ibraheem Jabir AlTalqani (Genius Journals, 2023)
The media contributes to the spread of intellectual and cultural awareness in various aspects of life, including the health aspect, particularly for individuals over forty. Thus, the purpose of this study was to determine “the role of the sports media in exercising for males over the age of forty.” The present investigation employed a descriptive analytical methodology, utilizing a questionnaire form as a research instrument. A sample of fortyfive men, aged between forty and forty-nine, who worked out in gyms was chosen. Following the distribution of the questionnaire form to the sample participants, the responses were examined
Keywords: examined; questionnaire; sample; responses